The correlation of islamic thought with relativity and cosmology - Nadiatul Mardiyah; Salis Raidalliani; Rizal Rizqi Al-Munir; Muhajir Muhajir; Muhammad Zaki Tamami (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
This research explores the correlation between Islamic principles and the theory of relativity and cosmology. Through detailed analysis, this article identifies points of convergence between Islamic concepts, such as the concept of divinity, continuity of the universe, and order in creation, with Einstein's principles of relativity and modern understanding of cosmology. By discussing in depth the perspectives of religion and science, this research not only explains the similarities in concepts, but also explores the potential for synergy between religious wisdom and scientific thinking. It is hoped that the results of this research can contribute to interdisciplinary discussions regarding the role of religion in detailing the secrets of the universe and provide a basis for dialogue between Islam, relativity and cosmology.